THE FEASIBILITY OF REFERRAL REWARD FOR SEREY TO ENTER THE INDONESIAN MARKET - Laksamana Darmawan (Diponegoro Journal of Accounting, 2022)
A referral reward system is an effective way to get new user. This method is critical to the company's marketing success since it can increase customer purchase intention and company brand image. A referral reward system is a consumer procedure of sending a company's marketing message to friends, family members, and coworkers via online media. When a person has strong social links in his or her online community. After the user done this, they will get a financial incentive from the company. Cryptocurrency will be the financial incentives since the company, serey is a blockchain based platform. This research studies the feasibility of Serey as a company entering Indonesian market using referral reward system. The study also gives information and difficulties for entering the Indonesian market by evaluating journals and scholarly articles and conducting a questionnaire-based survey. After conducting research, it is feasible to implement this method for Serey to enter Indonesian market. The respondent of questionnaire responds positively on this method. The majority have experiencing referral reward and interest to use this method.